The Effect of Giving Rewards on Students' Learning Interest in the Subject Grade IV SDN 1205 in Silejeng Sihapas Barumun District Padang Lawas Regency, Padangsidempuan, Indonesia - Syafnan; Fitriani HASIBUAN; Asriana HARAHAP (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This research is motivated by the application of learning methods that are less than optimal in increasing the active role of students during the teaching and learning process. One factor that plays an important role in learning is the provision of rewards, which can motivate students to be more enthusiastic in learning. Giving rewards creates a positive learning environment and encourages students to achieve more, and can increase their learning interest in a subject. Interest in learning itself is an encouragement in students, either consciously or unconsciously, which affects their involvement in learning activities. This study aims to determine the effect of giving rewards on students' interest in learning. This research uses a quantitative approach, which is research that processes numerical data to develop and apply a systematic analysis model. The research method used is experimental, with a true experimental design that allows control of external variables that can affect research results. Based on the results of the questionnaire data analysis regarding student interest in learning, the highest score was 40 and the lowest score was 32.